Characterization of the spontaneous and inoculated fermented soybean (Glycine max, var. PSB SY2) whey extracts for bacteriostatic activity as applied to raw pork loin slices - Valad-on, Klarshane D.
This study primarily aimed to investigate the bacteriostatic activity of spontaneous and inoculated fermented soy whey extracts to valorize soy whey and improve the shelf life of raw pork. Soy whey was produced and then sterilized in the laboratory from local soybeans (Glycine mac var. PSB SY2) of Cagayan Valley. Sterilized soy whey was divided into three batches: unfermented (USW), spontaneously fermented (S-FSW), and fermented with L. plantarum (I-FSW). Results revealed that all treatments were incapable of producing a significant zone of inhibition for E. coli UPCC 1195 and S. aureus UPCC 1143. Given the results, USW and only one representative for the fermented samples, I-FSW, were used to treat the pork samples. The study determined the changes in microbial counts and pH levels in raw pork loin slices applied with different treatments. Results indicated that I-FSW demonstrated minor inhibitory effects, which is shown by the decrease (-28.03%) in microbial counts. Meanwhile, U-SW had the highest increase (+54.3%) of microbial growth which could be attributed to its nutrient-rich composition and absence of fermentation in the treatment. It is likely that the lack of significant antimicrobial activity in I-FSW is caused by the insufficient concentration of bacteriocin present in the treatment. Moreover, an increase in the pH of the pork samples was also observed across all treatments. This can be due to the increased metabolic activity and protein degradation during storage. In conclusion, these findings show that although fermented whey from local soybeans (var. PSB SY2) inoculated with L. plantarum showed minimal bacteriostatic activity, the composition of the fermenting medium and the environment must still be adjusted to increase its ability to produce bacteriocins, and overall exhibit a higher bacteriostatic activity.